Management of storm drainage and flood control in new developments in Indonesia - Rahardjo, Hary Agus, author; Grigg, Neil S., advisor; Senior, Bolivar A., committee member; Smith, Freeman M., committee member; Criswell, Marvin E., committee member (Colorado State University. Libraries, 2002)
New residential developments in developing countries such as Indonesia generate adverse impacts and unsafe living conditions for various reasons, including vulnerability to flooding. The constraint faced by developing countries relates to absence of integrated land and water planning, lack of regulatory control, increasingly severe extreme events due to urbanization, lack of drainage system infrastructure, clogging by ad hoc structures and garbage, and lack of operation and maintenance systems.

Dealing with flood problems in newly constructed residential developments in Indonesia requires overall, integrated efforts. Problems are interrelated and form a vicious circle. Ongoing and unsolved drainage problems will make existing drainage worse. Flood problems will harm residents, and gradually influence local economic development. The lower economic status of society will hamper income of local government, which makes it unable to provide decent facilities for society. An unorganized community tends to lead lives according to individual preferences, with less attention to hygiene and decent environmental conditions, such as those related to storm drainage and flood control.

This study addresses the causes of flood problems in new residential developments by presenting a three-part management model with technical, institutional, and financial elements. The first objective of this study is to develop a comprehensive concept for storm drainage and flood control systems in new residential districts in developing countries. The other objective is to use the broad concepts developed to create a management model for this situation. The model is tested by analyzing how it applies to Indonesia, but it is intended for application to other countries as well.

The implementation of the management model in Indonesia resulted in important findings. Local government is not well organized; rules, laws and regulation are not complete; and enforcement for penalties must be tightened. Poor planning and design require technical capability improvement among local agencies. An appropriate method of sources of funds for storm drainage and flood control should be developed.

Considering that many other developing countries have even higher population growth than to Indonesia, the need for residential development is also higher than Indonesia. Thus, the case study based on Indonesia could become a representative example for other developing countries.
Keywords: civil engineering